IMPACT OF COMPLEXONS ON GAS-FORMATION IN GROUTING MORTAR FOR ENFORCING LOOSE ROCKS AT BED WELL BOTTOM ZONE - Alla A. Pereima; Ekaterina Yu. Kukulinskaya (Вестник Северо-Кавказского федерального университета)
When dealing with wells that have a destroyed bed well bottom zone it is useful to fill the caverns with grouting mortar, which, when hardens, makes an artificial manifold with due force and permeability. The item offers a description of a mechanism for physical-chemical interaction among the ingredients with gassing in mortar in view of different technologies employed to make it.